2012
DOI: 10.1007/s10557-012-6405-1
|View full text |Cite
|
Sign up to set email alerts
|

Dofetilide Promotes Repolarization Abnormalities in Perfused Guinea-pig Heart

Abstract: Proarrhythmic potential of dofetilide in guinea-pig heart is attributed to steepened electrical restitution, increased transepicardial variability in electrical restitution kinetics, amplified transmural dispersion of refractoriness, increased critical interval for ventricular re-excitation, and triangulation of epicardial action potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 47 publications
4
28
0
Order By: Relevance
“…Steepened electrical restitution may facilitate significant beat‐to‐beat alterations in action potential duration in the presence of fast beating rates, thus precipitating ventricular fibrillation . In this study, the maximum restitution slope was found to be significantly increased by procainamide ( Figure e ), which is in line with changes determined previously upon infusion of selective I Kr blocker such as dofetilide . In contrast, neither steady‐state APD 90 nor the steepness of electrical restitution was affected by lidocaine, a selective I Na blocker ( Figure b,d,f ).…”
Section: Discussionsupporting
confidence: 91%
“…Steepened electrical restitution may facilitate significant beat‐to‐beat alterations in action potential duration in the presence of fast beating rates, thus precipitating ventricular fibrillation . In this study, the maximum restitution slope was found to be significantly increased by procainamide ( Figure e ), which is in line with changes determined previously upon infusion of selective I Kr blocker such as dofetilide . In contrast, neither steady‐state APD 90 nor the steepness of electrical restitution was affected by lidocaine, a selective I Na blocker ( Figure b,d,f ).…”
Section: Discussionsupporting
confidence: 91%
“…Proarrhythmic modifications of ventricular repolarization by dofetilide were analysed in experimental studies. Consistent with spatial heterogeneities in the distribution of I Kr , dofetilide was found to produce non‐uniform lengthening of APD and/or the refractory period in canine, rabbit, and guinea‐pig hearts (Osadchii 2012c; 2012d, 2014c: studies IV, V, and X, respectively) . Over the transepicardial plane, dofetilide evokes a greater APD lengthening in LV than RV chamber, an effect that contributes to attenuated RV‐to‐LV activation–repolarization coupling, as evidenced by markedly reduced slope of the local APD‐to‐activation time linear relationships (Fig.…”
Section: Arrhythmogenic Responses To Antiarrhythmic Drugsmentioning
confidence: 73%
“…This change results in increased epicardial dispersion of repolarization time in dofetilide‐treated heart preparations, both during regular pacing and in extrasystolic beats (Osadchii 2014c: study X) . Across the LV wall, dofetilide provokes a greater prolongation of refractory periods at the endocardium compared to the epicardium, thus increasing the transmural dispersion of refractoriness (Osadchii 2012c, 2012d: studies IV and V, respectively) . Two other important attributes of dofetilide‐induced arrhythmogenicity appear to be the steepened electrical restitution, and abnormal temporal relations between ventricular APD and refractory period.…”
Section: Arrhythmogenic Responses To Antiarrhythmic Drugsmentioning
confidence: 99%
“…Experiments in these systems have demonstrated different arrhythmic risk markers, such as increased TDR given by the maximum APD difference across the myocardial wall [48], increased critical interval for re-excitation given by the APD-ERP difference [23], [49], [50], [51], shortened λ and reduced λ-TRIAD (which is based on λ and repolarization properties of triangulation, reverse use dependence, instability and dispersion: TRIaD) [52]. The clinical marker traditionally used for predicting arrhythmic risk has been QT c [53].…”
Section: Introductionmentioning
confidence: 99%